ANALYSIS FACTORS OF BREAST LESION CASE IN RSUD DR. SOETOMO SURABAYA - Wilda Fitria Rachmadina; Willy Sandhika; Widati Fatmaningrum (JURNAL WIDYA MEDIKA, 2022)
Introduction: Data from Indonesian Health Ministry stated that there was an increase in the prevalence of breast tumors in 2015 – 2017 by 1.8 per 100 to 21.3 per 100,000 women aged 30-50 years. The most common types of benign breast lesions found in women worldwide are fibrocystic changes of breast and fibroadenoma. Aim: This research aims to analyze the factors of age, age at menarche, parity, use of hormonal drugs, and family history with the incidence of benign breast lesions in RSUD Dr. Soetomo Surabaya. Methods: This research method is observational analytic with a case-control approach, consisting of a case group and a control group of 41 respondents in each group. The statistical test of the study used the Chi-Square Test, Independent t-test, Mann Whitney, and Odds Ratio (OR). Results: The results of statistical tests obtained age factor p(sig)=0.002, hormonal use p(sig) 0.000, family history p(sig) 0.016, age at menarche p(sig) 0,282, and parity p(sig) 0.568. Conclusion: Conclusion there is a relationship between age, use of hormonal drugs, and family history and there is no relationship between age at menarche and parity with the incidence of benign breast lesions in RSUD Dr. Soetomo Surabaya. Family history has an Odds Ratio (OR) of 4.796. Keywords: Breast Lesions, Reproductive Health